2016
DOI: 10.1016/j.ijnurstu.2015.08.011
|View full text |Cite
|
Sign up to set email alerts
|

Care workers health in Swiss nursing homes and its association with psychosocial work environment: A cross-sectional study

Abstract: Physical and mental health among care workers in Swiss nursing homes is of concern. Modifying psychosocial work environment factors offer promising strategies to improve health. Longitudinal studies are needed to conduct targeted assessments of care workers health status, taking into account their age, along with the exposure to all four domains of the proposed WHO model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
39
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 44 publications
4
39
0
3
Order By: Relevance
“…The study showed that presenteeism was most common among care assistants and that its prevalence among nursing professionals did not deviate from that among the all other occupations group. The high prevalence of presenteeism found among care assistants is in line with findings from studies from other countries [3][4][5][6]11,20,[27][28][29]. Unlike the present study, other studies have found that nursing professionals have higher levels of presenteeism than other occupations [7,9,16,17,30].…”
Section: Discussionsupporting
confidence: 90%
“…The study showed that presenteeism was most common among care assistants and that its prevalence among nursing professionals did not deviate from that among the all other occupations group. The high prevalence of presenteeism found among care assistants is in line with findings from studies from other countries [3][4][5][6]11,20,[27][28][29]. Unlike the present study, other studies have found that nursing professionals have higher levels of presenteeism than other occupations [7,9,16,17,30].…”
Section: Discussionsupporting
confidence: 90%
“…Although healthcare professionals may often feel satisfied with their work,1 they are particularly at risk of numerous physical and psychological health problems, including back pain (eg, prevalence among home nurses: 19%),2 depression (prevalence among medical doctors: 28.8%)3 and suicide (twofold increase in incidence among nurses and physicians) 4. Furthermore, between 2011 and 2014, the rate of burnout in American physicians increased from 45% to 54% 5.…”
Section: Introductionmentioning
confidence: 99%
“…Research shows that PSWs experience stress due to the nature of their work and work environments in Canada and elsewhere including U.S., UK, Europe, and Japan [3, 7, 11–13, 15–17, 21, 24]. Similarly, nurses, nursing aides, nursing assistants and nursing health care staff employed in elderly care in long-term care facilities/ nursing homes in Canada [25], Japan [26], Taiwan [20] Switzerland [27], Finland [28], U.S. [29] and UK [30] report stress at work. The stress in health care environments is so unique to the sector that it is sometimes referred as a ‘stress of conscience’ where health care staff experience a troubled conscience because they would like to provide the best quality care but are unable to do so [31] for a variety of reasons.…”
Section: Introductionmentioning
confidence: 99%
“…For nurses in Ontario, Canada research showed that as the importance of income for their family’s well-being increased so did their stress level [39]. The work characteristic of workload is shown to be associated with the work stress of health care workers [10, 20, 2729, 31, 36, 38, 40, 41] and this factor is included as a control variable in our study.
Fig. 1The conceptual model of organizational practices associated with PSWs life and work stress
…”
Section: Introductionmentioning
confidence: 99%